Governance of Presidential Elections: Dynasty Politics and Institutional Ethics - Razak, Muhammad Rais Rahmat; Adnan, Andi Astinah; Aris, Affandi Agusman (Universitas Muhammadiyah Yogyakarta, 2025)
The governance of the 2024 Presidential Election leaves an important note for democracy in Indonesia. The President as head of State is considered not neutral, weakening state institutions practicing dynasty politics in a democratic country. This study aims to determine the practice of presidential dynasty politics and the ethics of state institutions in the 2024 national leadership succession. Using a descriptive-qualitative approach with an in-depth analysis method of the state process and the President's response in facing the leadership succession. Data collection was conducted through media coverage analysis and a literature review from previous studies. The results show that the involvement of the President strengthens dynasty politics through policies and decisions of the Constitutional Court, which are considered not neutral, so they can weaken democratic ethics. This fact is something new in the practice of democracy in Indonesia, and it has an impact on the integrity of state institutions and election organizers. This study reveals a new perspective on the President's involvement in dynastic politics and its implications for the ethical governance of state institutions during the 2024 presidential election. These findings contribute to the understanding of the challenges of Indonesian democracy and their potential impacts on the 2024 regional head elections, emphasizing the need to strengthen integrity in the democratic process.